2021
DOI: 10.1523/jneurosci.2848-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

4R Tau Modulates Cocaine-Associated Memory through Adult Dorsal Hippocampal Neurogenesis

Abstract: The development, persistence and relapse of drug addiction require drug memory that generally develops with drug administration-paired contextual stimuli. Adult hippocampal neurogenesis (AHN) contributes to cocaine memory formation; however, the underlying mechanism remains unclear. Male mice hippocampal expression of Tau was significantly decreased during the cocaine-associated memory formation. Genetic overexpression of four microtubule-binding repeats Tau (4R Tau) in the mice hippocampus disrupted cocaine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…In the present study, we explored the mechanism by which Fyn mediates cocaine-associated memory formation. We found that cocaine exposure increases Fyn activity in the hippocampus and that Fyn may regulate Tau expression, which plays an important role in cocaineassociated memory formation (Li et al, 2021). Our results suggested that inactivation of the Src kinase Fyn in the hippocampus significantly disrupts cocaine-induced seeking behaviours in a self-administration paradigm and a cocaine-CPP paradigm without altering locomotor activity.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In the present study, we explored the mechanism by which Fyn mediates cocaine-associated memory formation. We found that cocaine exposure increases Fyn activity in the hippocampus and that Fyn may regulate Tau expression, which plays an important role in cocaineassociated memory formation (Li et al, 2021). Our results suggested that inactivation of the Src kinase Fyn in the hippocampus significantly disrupts cocaine-induced seeking behaviours in a self-administration paradigm and a cocaine-CPP paradigm without altering locomotor activity.…”
Section: Discussionmentioning
confidence: 57%
“…Tau, a microtubule-associated scaffolding protein, was shown to be necessary for drug-associated memory formation in our previous study (Li et al, 2021). In our previous research, we first found that Tau expression is significantly downregulated in the hippocampus during cocaine-associated memory formation, promoting adult hippocampal neurogenesis in the hippocampal dentate gyrus and facilitating enhanced cocaineassociated memory formation (Li et al, 2021). Nevertheless, the mechanism underlying the reduction in Tau levels during cocaine-associated memory formation remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…However, the changes in MAPs expression during learning and memory do not always comprise more protein synthesis, as opposite changes have also been found [162]. For instance, both Tau long isoforms expression and Tau-dependent P13K signaling are decreased during cocaine-associated memory formation, which was abolished by Tau overexpression [162]; when extinction is achieved in this paradigm, Tau long isoforms return to basal levels [162]. It is possible that learning-dependent expression changes in these Tau isoforms drive the dynamic state of neuronal MTs [163].…”
Section: Microtubular Reconfiguration During Brain Functionmentioning
confidence: 99%
“…Memory consolidation is accompanied by increased expression of MAP2 and β-tubulin [155][156][157][158], which is reflected in increased MAP2 immunohistochemical staining [159][160][161]. However, the changes in MAPs expression during learning and memory do not always comprise more protein synthesis, as opposite changes have also been found [162]. For instance, both Tau long isoforms expression and Tau-dependent P13K signaling are decreased during cocaine-associated memory formation, which was abolished by Tau overexpression [162]; when extinction is achieved in this paradigm, Tau long isoforms return to basal levels [162].…”
Section: Microtubular Reconfiguration During Brain Functionmentioning
confidence: 99%
“…GSK-3β is involved in the development of behavioral sensitization to the locomotor activating effects of cocaine in rats [ 190 ], and cocaine withdrawal disrupts the circadian regulation of GSK-3β [ 191 ]. Knockout of Tau enhances cocaine conditioned place preference in mice while Tau overexpression in the hippocampus suppresses cocaine conditioned place preference [ 192 ]. The identification of parallel pathways for the regulation of psychostimulant response in flies and mammals has implications for the identification of novel regulators of psychostimulant response.…”
Section: Studying Psychostimulant Abuse With Drosophilamentioning
confidence: 99%